The Qualified Effects Doctrine in the Extraterritorial of Competition Law Application: An Indonesia Perspective - Sukarmi Sukarmi; Hassan Qaqaya; Fransiska A. Susanto; Rika Kurniaty (Faculty of Law, Sriwijaya University, Indonesia, 2021)
The use of extraterritorial jurisdiction of competition law, based on the effect doctrine, has long been debated. This paper discusses the application of extraterritorial jurisdiction to Indonesian competition law. Competition law in Indonesia applies to any collusive or abusive behaviour that has a necessary effect on the business and economy spheres, regardless of the nationality or geographic location of the company or where the occurred conduct. This study employs a normative juridical method to analyse legal norms and principles. The approaches used include a statutory approach, a comparative law approach, and a case approach. This study reveals that the regulations concerning the prohibition of monopolistic practices and unfair business competition have not explicitly regulated extraterritorial norms in Indonesia. However, the Business Competition Supervisory Commission makes legal breakthroughs by applying the extraterritorial principle to resolve the involvement of foreign business actors and impose penalties on them. This article argues that Indonesia significantly needs to amend its competition law and increase cooperation with other countries to enforce the competition law.